Pengembangan Buku Ajar Bahasa Arab Berbasis Permainan Edukatif Kosakata Dan Kalimat Bahasa Arab - Nur Ainun Septyningrum; Aufia Aisa (QALAM: JURNAL PENDIDIKAN ISLAM, 2022)
his research is motivated by the lack of students at MA Al-Bairuny Jombang in mastering Arabic vocabulary so that it affects the low interest and learning achievement. This is because the learning process that takes place is only done conventionally which in the end causes students to tend to be passive and easily bored in learning Arabic. Therefore, this research aims to develop Arabic textbooks based on Arabic vocabulary and sentence educational games as a solution to overcome the lack of students' Arabic vocabulary mastery. The method used in this research is RD by adopting the ADDIE model. The subjects in this study were students of class X IPS 1 MA Al-Bairuny Jombang, totaling 25 children. Data collection instruments used in the form of interviews, questionnaires and tests. The types of data analyzed produce qualitative and quantitative data including: 1) teaching materials have been developed in the form of Arabic textbooks based on Arabic vocabulary and sentences educational games. 2) based on the validity test, the textbook developed reached a very valid feasibility level with an average of 93,33% from material experts and 83,57% from media experts. 3) the level of effectiveness of the textbooks is very effective, seen from the comparison of the pre-test scores reaching an average of 0% and the post-test reaching an average of 88%